Transformasi Digital dalam Sistem Perpajakan Daerah: Apakah Memperkuat Faktor Utama Kepatuhan Pajak? - Ali Abrori; Unggul Purwohedi; Muhammad Yusuf (Research and Development Agency Ministry of Home Affairs, 2024)
The contribution of local taxes to the subnational government budget was minimal. The average local tax ratio in Indonesia is only 1,21%. Consequently, subnational governments remain highly dependent on transfers from the central government. Therefore, understanding the factors that influence tax compliance is essential for easing the central government's budget constraints and strengthening local government self-reliance. This study examines the relationship between tax morale, tax awareness, and tax service quality in shaping tax compliance in Jakarta Province. In addition, this study explores how digital transformation affects the relationship between these factors and tax compliance. The research methodology is quantitative, where the Partially Least Square-Structured Equation Model (PLS-SEM) is employed. The data was collected through questionnaires on land and building tax at UPPD Kelapa Gading, a local tax office in Jakarta. Using convenience sampling, we obtained 188 valid respondents for analysis. The finding concluded that tax morale and tax service quality positively affect the taxpayer. On the other hand, tax awareness has no significant effect on tax compliance. Meanwhile, the implementation of information technology to streamline the business process was effective in improving the relationship between tax awareness and tax service quality to tax compliance but has minimal effect on tax morale. This finding implies that enhancing tax compliance requires both internal and external perspectives. Meanwhile, solely improving taxpayers' knowledge has a minimal impact. Furthermore, digital transformation effectively enhances external factors, such as tax awareness and tax service quality, by providing taxpayers with easy access to reporting, notification, and paying taxes.